Sediment Resuspension and Deposition on Seagrass Leaves Impedes Internal Plant Aeration and Promotes Phytotoxic H2S Intrusion - Brodersen, Kasper E.; Hammer, Kathrine J.; Schrameyer, Verena; Floytrup, Anja; Rasheed, Michael A.; Ralph, Peter J.; Kühl, Michael; Pedersen, Ole (Frontiers in Plant Science, 2017)
Anthropogenic activities leading to sediment re-suspension can have adverse effects on adjacent seagrass meadows, owing to reduced light availability and the settling of suspended particles onto seagrass leaves potentially impeding gas exchange with the surrounding water. We used microsensors to determine O2 fluxes and diffusive boundary layer (DBL) thickness on leaves of the seagrass Zostera muelleri with and without fine sediment particles, and combined these laboratory measurements with in situ microsensor measurements of tissue O2 and H2S concentrations. Net photosynthesis rates in leaves with fine sediment particles were down to ~20% of controls without particles, and the compensation irradiance increased from a span of 20-53 to 109-145 µmol photons m-2 s-1. An ~2.5-fold thicker DBL around leaves with fine sediment particles impeded O2 influx into the leaves during darkness. In situ leaf meristematic O2 concentrations of plants exposed to sediment re-suspension were lower than in control plants and exhibited long time periods of complete meristematic anoxia during night-time. Insufficient internal aeration resulted in H2S intrusion into the leaf meristematic tissues when exposed to sediment resuspension even at relatively high night-time water-column O2 concentrations. Re-suspended sediment particles that settle on seagrass leaves thus negatively affect internal tissue aeration and thereby the plants resilience against H2S intrusion.